Pengaruh Motivasi dan Komitmen Organisasi terhadap Kinerja Account Representative KPP Pratama Badung Utara dengan Etos Kerja sebagai Variabel Moderasi - Agustinus Triyanto; M. Rudi Irwansyah; Kadek Rai Suwena (Universitas KH. Abdul Chalim Mojokerto, 2026)
Public sector organisations are required to demonstrate optimal performance as a form of accountability to the public, particularly in delivering effective services oriented toward public interest. Account Representative (AR) performance, as the frontline of Badung Utara Tax Office, plays a strategic role in supporting taxpayer compliance and achieving state revenue targets. However, revenue realization at Badung Utara Tax Office has not yet reached the established targets. This study aims to analyze the effect of work motivation and organisational commitment on Account Representative performance at Badung Utara Tax Office, as well as to test the moderating role of work ethic. The research employs a quantitative approach using a survey method. Data were collected through questionnaire distribution to AR at Badung Utara Tax Office and analysed using statistical analysis techniques and PLS-SEM to test the relationships among variables. Work motivation and organisational commitment are positioned as independent variables, AR performance as the dependent variable, and work ethic as the moderating variable. The research results indicate that work motivation has a positive and significant effect on AR performance. Similarly, organisational commitment is proved to provide a substantial contribution to performance improvement. Furthermore, work ethic is proven to moderate the effect of work motivation on AR performance, thereby strengthening the manifestation of motivation into consistent work behaviour orientated toward public service. However, work ethic does not moderate the effect of organisational commitment on AR performance. This research is expected to provide practical contributions for human resource management within Badung Utara Tax Office to enhance employee performance sustainably.